LINGUISTIC AND TRANSLATION STUDIES OF ECOLOGICAL TERMINOLOGY: A COMPARATIVE ANALYSIS - Ruziyeva Muhayyo Baxtiyor qizi (International Journal of Literature and Language Studies, 2026)
In this scientific article, ecological terminology, considered one of the most urgent directions of modern linguistics, is comprehensively investigated based on linguistic and translation principles. Global climate changes and the development of the green economy lead to the intensive formation of new ecological concepts within the linguistic system. Ecological terms in the English and Uzbek languages were selected as the object of research, and their derivational-semantic features, morphemic structure, and equivalence problems during translation into Uzbek were systematically analyzed. Using a comparative methodology, conceptual asymmetries between the two languages were revealed, and scientific recommendations were developed to minimize semantic losses in translation.